FULL-TARGETED ASPECTS OF MONITORING OF ELECTRICITY LEVELS AT ENTERPRISES OF THE INDIVIDUAL DEPARTMENT OF THE KRIIVORIZHOGY REGION - I.O. Sinchuk (Elektrotehnìka ta Elektroenergetika, 2018)
Purpose. Conduct a cost-target analysis as part of monitoring electricity consumption levels and develop recommendations for a rational strategy for consuming electricity from mining enterprises with underground mining of iron ore. Methodology. The study is based on the use of laws, regularities and categorical apparatus. In the process of scientific research, general scientific methods of research (comparison, generalization, analogy method, structural analysis and synthesis), methods of logical-theoretical analysis, special economic-mathematical methods were used. Findings. The indicators of electricity consumption at iron ore enterprises of the Krivoy Rog region are analyzed. A comparative analysis of the planned and actual energy consumption is carried out. The trend components of electricity consumption indicators at iron ore enterprises of the Krivoy Rog region are highlighted. Dynamics of structural transformation of unit cost of electric energy production at iron ore enterprises of the Krivoy Rog region is determined. Originality. When forming the cost-target component of monitoring the energy consumption levels, it is suggested to use the index methodology in combination with trend models, which will allow to determine the forecast of electricity consumption and realize rational management of power consumption. An index system of structural transformation of the unit cost of electric energy production at mining enterprises of the Krivoy Rog region is proposed. Practical value. Dynamics analysis of the structural transformation of the unit cost of electric power consumption of iron ore enterprises of the Krivoy Rog region is carried out. The system of indices of the unit cost of electricity consumption is defined: the index of the average unit cost of electricity consumption of variable composition; index of unit cost of power consumption of fixed composition; the index of the average unit cost of power consumption of structural shifts. The deterministic component of the time series of electricity consumption for the iron ore enterprises of the Krivoy Rog region was singled out and analyzed. The obtained trend models give grounds for determining the forecast of electricity consumption levels with an appropriate level of reliability. The indicators of electricity consumption levels provide the formation of an information-analytical component of the relevant monitoring. The carried out researches allow to formulate the strategy of electricity consumption at the enterprises of iron ore industry of the Krivoy Rog region. The problems highlighted in the article are closely related to the scientific and practical tasks of rational use and distribution of available energy resources.